Alien domesticity: representing home during a pandemic. (February 2023) - Luvaas, Brent
Cultural geography and the related disciplines of urban sociology and anthropology have long focused their theoretical lenses on the city as a space of lived multiplicity. This photographic essay focuses its lens on the home as such a space. During the pandemic lockdown of 2020–2021, many of us spent more time in our homes than we ever had before, working, teaching, schooling, shopping, and barricading ourselves from the outside world. This essay borrows from the often ambiguous and anonymizing aesthetics of street photography to depict the multiple, overlapping worlds of home during a pandemic. Home, as depicted here, is an always unfinished process of affective assemblage and dissolution. The images featured seek to capture that lack of resolution, the messy emotional texture of home life under lockdown.